Comparison of the Effectiveness of Acceptance and Commitment Therapy Matrix (ACTM) and Emotion-Focused Therapy (EFT) on Family Adaptability and Emotional Self-Regulation in Women with Marital Conflict - Hashemizadeh , Fatemeh Sadat; Atashpour, Seyed Hamid; Farhadi, Hadi (Psychology of Woman Journal, 2024)
Objective: This study aimed to compare the effectiveness of the Acceptance and Commitment Therapy Matrix (ACTM) and Emotion-Focused Therapy (EFT) on family adaptability and emotional self-regulation in women with marital conflict. Methods and Materials: The research method was quasi-experimental in three stages: pre-test, post-test, and follow-up. Out of approximately 154 women with marital conflict identified through purposive sampling using the Marital Conflict Questionnaire by Kanth Akman, 45 women were selected and randomly assigned to two experimental groups and one control group, with 15 participants in each group. Each experimental group underwent 10 sessions of ACTM and EFT, respectively, while the control group received no treatment. All three groups were assessed before, after, and one month following the intervention using the Family Adaptability Questionnaire by Olson and the Emotional Self-Regulation Questionnaire by Hoffman and Kashdan. The data were analyzed using repeated measures analysis of variance and post-hoc tests. Findings: The results indicated that ACTM was significantly effective in the family adaptability component of women with marital conflict (p < 0.05), while Emotion-Focused Therapy did not show a significant effect. Both treatments significantly impacted emotional self-regulation compared to the control group. Conclusion: Therefore, it is suggested to use the ACT Matrix for family adaptability and both therapies for the emotional self-regulation component.